Embracing Pedagogical Pluralism:An Educator’s Case for (at Least Public) School Choice - Ferrero, David J. (Education Policy Analysis Archives, 2003)
Pedagogical and curricular beliefs and commitments are expressions of deeper philosophical and ideological worldviews that empirical research can sometimes modify but not ultimately eliminate. The pluralism these views produce is reasonable in that they all represent plausible interpretations of liberal-republican values and professional standards of practice; they should be granted some room to flourish under a system of carefully regulated autonomy and choice. Three objections to a conception of school choice grounded in a notion of reasonable pluralism among educational doctrines are addressed: 1) that it would undermine educators' efforts to secure status for themselves as professionals by admitting that “best practices” in education offer rough guidance at best; 2) that it would leave parents and students vulnerable to quackery; 3) that it abandons the common school tradition and its aspirations. I conclude with an examination of why the conceptual basis on which a society designs a system of choice makes a difference.